FROM GRASSROOTS FEMINIST MOBILIZATION TO POLICY CHANGE: THE ANTI-ARRACK WOMEN’S MOVEMENT IN ANDHRA PRADESH, INDIA (1992) - Mittal, Sangeeta; Mona (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Anti-Arrack Movement of early 1990s Andhra Pradesh is a compelling case of grassroots feminist mobilization translating into substantive policy change. Spearheaded by rural women across caste and class divisions, the movement arose in response to the devastating socioeconomic impacts of rampant alcohol consumption — from crippled family incomes to intensified domestic violence — even as the state enriched itself on arrack excise revenues. Drawing on historical accounts, this paper traces how women’s shared experiences of deprivation and abuse coalesced into a sustained public campaign that forced the state to ban arrack in 1993 (and adopt total prohibition by 1995). Situating the Anti-Arrack agitation within a broader context of bottom-up governance reform, the study illustrates how non-elite actors can reshape state priorities through persistent civic action. The movement’s evolution from localized, literacy-driven awakening to state-wide protests (marches, sit-ins, and media campaigns) underscores the agency of marginalized women in reconfiguring state-citizen relations. Ultimately, the movement’s trajectory offers vital insights into how collective action from the grassroots can disrupt entrenched power structures and redefine the very agenda of development.